If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 3 = -1(x + -33) Reorder the terms: 3 + 5x = -1(x + -33) Reorder the terms: 3 + 5x = -1(-33 + x) 3 + 5x = (-33 * -1 + x * -1) 3 + 5x = (33 + -1x) Solving 3 + 5x = 33 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 3 + 5x + x = 33 + -1x + x Combine like terms: 5x + x = 6x 3 + 6x = 33 + -1x + x Combine like terms: -1x + x = 0 3 + 6x = 33 + 0 3 + 6x = 33 Add '-3' to each side of the equation. 3 + -3 + 6x = 33 + -3 Combine like terms: 3 + -3 = 0 0 + 6x = 33 + -3 6x = 33 + -3 Combine like terms: 33 + -3 = 30 6x = 30 Divide each side by '6'. x = 5 Simplifying x = 5
| 2(4k+6)=3(5k+1) | | 87-6x=12x+23 | | 8x-5y=5 | | 6-8x=93-29x | | -90-9x=10x | | 6x*2= | | 5(1-x)-2=3x-4 | | 3x-1=14x+7 | | 117-4x=32x+17 | | 8-9x=96-37x | | -14-10x=8x+23 | | 2x-1=12-81 | | 5x-25=35 | | 2(5x-4)=4(x+7) | | (5x+6)(x-1)-(2x-5x+3)=0 | | X^3=36 | | 2n^3+7=2n^5 | | 140-7x=38x+15 | | 5n+7=27 | | (n-6)*2=4 | | (n-6)*10=70 | | 65=-4(5b+3) | | 108-3x=4x+17 | | 14-6x=6-8x | | 7(2y-3)=28 | | 8x^3+4x^2-34x+15=0 | | -3(4-2w)=10 | | 3(4-3s)=34 | | 3g+15=5g-3 | | 9x+23=3x+197 | | -3(4-2n)=19 | | -3(4-2)=19 |